A kit and handbook for the study of simple electric circuits - Pascua, Gregorio A. 1938- (1974)
This paper is concerned with the design, construction, use and repair of a kit for the study of simple electric circuits. The study is comprised of two phases, namely: instrumentation and curriculum making in the sense that innovative curriculum materials in the form of a handbook and experiments have been written.
Thesis (M.A.T.Physics)--University of the Philippines.
Keywords: Physical instruments; Electric circuits -- Handbooks, manuals, etc